A Binational Multicenter Pilot Feasibility Randomized Controlled Trial of Early Goal-Directed Mobilization in the ICU*. Issue 6 (June 2016) - Hodgson, Carol L.; Bailey, Michael; Bellomo, Rinaldo; Berney, Susan; Buhr, Heidi; Denehy, Linda; Gabbe, Belinda; Harrold, Megan; Higgins, Alisa; Iwashyna, Theodore J.; Papworth, Rebecca; Parke, Rachael; et al.
Abstract : Objectives: To determine if the early goal-directed mobilization intervention could be delivered to patients receiving mechanical ventilation with increased maximal levels of activity compared with standard care. Design: A pilot randomized controlled trial. Setting: Five ICUs in Australia and New Zealand. Participants: Fifty critically ill adults mechanically ventilated for greater than 24 hours. Intervention: Patients were randomly assigned to either early goal-directed mobilization (intervention) or to standard care (control). Early goal-directed mobilization comprised functional rehabilitation treatment conducted at the highest level of activity possible for that patient assessed by the ICU mobility scale while receiving mechanical ventilation. Measurements and Main Results: The ICU mobility scale, strength, ventilation duration, ICU and hospital length of stay, and total inpatient (acute and rehabilitation) stay as well as 6-month post-ICU discharge health-related quality of life, activities of daily living, and anxiety and depression were recorded. The mean age was 61 years and 60% were men. The highest level of activity (ICU mobility scale) recorded during the ICU stay between the intervention and control groups was mean (95% CI) 7.3 (6.3–8.3) versus 5.9 (4.9–6.9), p = 0.05. The proportion of patients who walked in ICU was almost doubled with early goal-directed mobilization (intervention n = 19 [66%] vs control n = 8 [38%]; p = 0.05). There was no difference in total inpatient stay (d) between the intervention versus control groups (20 [15–35] vs 34 [18–43]; p = 0.37). There were no adverse events. Conclusions: Key Practice Points: Delivery of early goal-directed mobilization within a randomized controlled trial was feasible, safe and resulted in increased duration and level of active exercises. Abstract : Supplemental Digital Content is available in the text.